Communicative Hospitality: Acts Of Service Among Front Desk Hotelier - Roy Bigwanto; Iwan Joko Prasetyo; Nurannafi Farni Syam Maella (SEAN Institute, 2024)
The study seeks to explore how the communication practices of front desk personnel, who interact primarily with hotel customers, influence the overall quality of the hospitality experience. The current body of research on hotel management emphasizes the crucial role of communication in providing outstanding service. It is crucial to develop a deeper understanding of the communication strategies and interpersonal abilities utilized by front desk hoteliers, and how these aspects influence visitor satisfaction and loyalty. Robert K. Yin's case study methodology entails engaging in extensive interviews with front desk personnel, closely observing their interactions with visitors, and thoroughly analyzing pertinent organizational documents. By considering a range of perspectives, individuals can gain a deeper understanding of the intricate dynamics between different forms of communication, the delivery of services, and the overall hotel environment. The findings suggest that providing exceptional hospitality service relies on effective communication, characterized by understanding, attentive listening, and a sincere commitment to meeting guests' needs. The study investigates how different management approaches and organizational cultures influence the communication behaviors of front desk staff in a hotel setting. As a result, this has an impact on guest satisfaction, loyalty, and the overall perception of the hotel brand. The findings of this study enhance the current scholarly knowledge regarding the role of communication in the hotel industry. Additionally, they provide practical implications for front desk training programs and hotel management. This article emphasizes the significance of fostering a culture of outstanding communication among front-line personnel to prioritize the communicative aspects of hospitality. This will assist in preserving a competitive edge in the ever-changing hotel industry and improving the overall satisfaction of our guests.